Filifolinone, a Natural Compound with Adjuvant Effect for Optimization of a Commercial Vaccine for Ipnv - Imarai-Bahamonde, C; Modak-Canobra, B; Valenzuela-Montenegro, B; Negrete-Vergara, C; Negrete-Vergara, C; Parra-Mardonez, N (Academic Press, 2019)
Sin Resumen Disponible